PENGEMBANGAN RPP BERBASIS MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN KEMANDIRIAN BELAJAR SISWA - Lisma Nurazizi; Bistari Bistari; Siti Halidjah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThis research aims to analyze the development of lesson plans based on PBL model to improve student learning independence in mathematics subjects in grade IV of SDN 27 Pontianak Tenggara. The method used in this research is research and development that was developed with the ADDIE model. Data collection techniques used are direct observation techniques and indirect communication by questionnaire and observation. Based on the calculation of the average percentage of the learning independence questionnaire that obtained the results of the first and second questionnaires there was an increase of 0.54%, from the second and third questionnaires there was an increase of 0.1% while the third and fourth questionnaires increased by 3%. If seen from the student activity sheet from the results of Lesson Plan 1 revision 1 and Lesson Plan 2 revision 1 decreased 1.49%, while Lesson Plan 2 revision 1 and Lesson Plan 1 revision 2 an increase of 3.6%, and Lesson Plan 1 revision 2 and Lesson Plan 2 revision 2 an increase of 1.61%. This proves that the development of lesson plans based on PBL models can improve student learning independence in mathematics subject in grade IV of SDN 27  Pontianak Tenggara. Keywords: Development, Learning Independence, Problem Based Leaning